When neglected species gain global interest: Lessons learned from quinoa's boom and bust for teff and minor millet - Andreotti, Federico; Bazile, Didier; Biaggi, Maria Cristina; Callo-Concha, Daniel; Jacquet, Julie; Jemal, Omarsherif M.; King, Oliver I.; Mbosso, C.; Padulosi, Stefano; Speelman, Erika N.; van Noordwijk, Meine (Elsevier, 2022)
Until recently, many so-called neglected and underutilized species (NUS) were not present in global markets despite playing a pivotal role in the local livelihoods in their places of origin. Today, some NUS receive substantial global interest and face growing global demands. Sudden increases in consumer demand trigger prices to rise; land-use change at the farm and national levels results in a rapid production increase. This phenomenon is known as “boom” and is usually followed by a “bust”, a rapid decrease in prices, and subsequently, production. This review elaborates on the boom-and-bust phases of two NUS: quinoa from the Andes and teff from Ethiopia. We explored the potential upcoming boom of minor millets in India. Our study proposes a generic framework for exploring cross-scale interactions and rethinking sustainability pathways for future NUS booms.